Review on Comparison of Single Stage and Multistage and Dry-Wet Anaerobic Digestion for Biomethane Production and Evaluation the Waste Management Strategy - Perera, Hasith; Shen Hosan; Vimukthi VITHANAGE; Dasith WIJESEKARA; Niroshan GUNAWARDHANA; Vimukthi THARAKA; Koswattage K. R; Shakya ABEYSINGHE (RADINKA JAYA UTAMA PUBLISHER, 2025)
The circular bioeconomy depends on anaerobic digestion technology to obtain energy from waste materials while minimizing ecological contamination. The research looks at how well single-stage and multi-stage anaerobic digestion systems work, comparing their advantages and disadvantages by examining design elements, stability conditions, and the amount of biogas produced from different types of feedstock. A comparison study evaluated the benefits together with restrictive factors and real-world uses of single-stage and multi-stage anaerobic digestion systems. The examination used microbial stability as well as biogas production rates, cost-effectiveness, and compatibility with various feedstocks to determine the various factors. Single-stage anaerobic digestion systems produced cost-effective operation along with simple management, which benefits small-scale facilities operating on uniform organic waste. Their microbial stability was restricted, which eventually led to diminished biogas production output. Multi-stage anaerobic digestion systems are more expensive to set up and keep running, but they allow for better control of the process and produce more biogas when dealing with a mix of agricultural waste and regular trash. System design stands as a fundamental element that determines the results of anaerobic digestion processes. The selection between single-stage or multi-stage systems depends on whether waste streams are simple and uniform or complex. Future development of anaerobic digestion technology requires concentration on lowering operating expenses along with the implementation of time-sensitive monitoring equipment and integration with clean energy facilities. The development of these steps represents fundamental requirements for establishing the sustainable scalability of anaerobic digestion systems as the primary waste management technology.